Fractality in the business management: an approach from the complexity - Cisneros Trujillo, Grace Milagros (2021)
The fractal paradigm has emerged as a significant framework within the realm of business management, offering insights into organizational dynamics in complex and rapidly changing environments. This study explores the applications of fractality across various organizational contexts, emphasizing its role in enhancing adaptability, resilience, and efficiency. Key examples include the Safety Fractal Analysis method (Accou & Reniers, 2019), which improves safety management systems through structured investigations of accidents, and the implementation of fractal enterprise models (Bider et al., 2017), which facilitate process optimization in diverse sectors. The findings underscore the importance of fostering a cultural shift towards collaboration and knowledge sharing among all organizational levels to effectively leverage fractal principles. Ultimately, this research highlights the potential of fractality to transform traditional management practices, offering pathways for sustainable innovation and growth in the face of globalization and complexity.